A Bibliometric Analysis: Problem Based Learning in Digital and Virtual Science Learning Environments - Safina Ridka Pratiwi; Dwikoranto Dwikoranto; Indri Hapsari Khansa; Lindsay Natalia Bergsma (Journal of Law and Bibliometrics Studies, 2026)
Objective: This study aims to analyze research trends in Problem-Based Learning (PBL) in digital and virtual science learning environments during the period 2015–2025. The analysis focuses on identifying dominant research themes, mapping the structure of the research field, and examining the evolution of research on the integration of digital technologies in science learning. Method: This study employed a bibliometric analysis of publications indexed in the Scopus database. The article selection process followed the PRISMA guidelines, yielding 101 documents for analysis. The study examined keyword co-occurrence, citation patterns, and thematic structures. Network, overlay, and density visualizations were conducted using VOSviewer to explore relationships between keywords and the temporal development of research topics. Results: The findings indicate that research on PBL in digital and virtual science learning is structured around core themes such as problem-based learning, students, e-learning, and virtual reality, which show strong interconnections. The temporal analysis reveals a shift from general educational contexts toward the integration of digital and immersive technologies, including virtual reality, augmented reality, and artificial intelligence. In addition, density and citation analyses highlight the central role of digital technology in shaping contemporary PBL research. In contrast, emerging topics such as machine learning and digital twins remain less explored. Novelty: This study provides a comprehensive bibliometric mapping of the convergence between PBL and digital–virtual technologies in science learning, revealing a conceptual shift toward intelligent and immersive learning environments and identifying emerging research opportunities.